Visual estimation of blood loss during caesarean section a prospective review / Tan Wei Keang - Tan, Wei Keang (2017)
One of the major threats to women during childbirth is excessive bleeding. Visual estimation of blood loss has been known to be inaccurate and imprecise, may contribute to delay institution of adequate resuscitation. Our objectives are to compare the blood loss estimated between anaesthetists and obsetetrician and assess their accuracy. METHODS: A prospective study done in UMMC included 147 pregnant women who underwent lower segment caesarean section fulfilling inclusion criteria. lntraoperative blood loss was assessed by both the anaesthetit and obstetrician on duty via visual estimation. The preoperative and postoperative haemoglobin level were obtained in order to calculate the amount of blood loss using a modified formula based on Gross. RESULTS: There was no significant difference in terms of blood loss estimated by anaesthetists and obstetricians. Visual estimation by these 2 groups of healthcare providers was inaccurate based on interclass coefficient analysis and assessment via the Bland and Altman plot. However, the background and seniority of the assessing health care providers did not affect the accuracy of the estimation. CONCLUSION: The visual estimation of blood los between anaesthetists and obstetrician during LSCS wa comparable, however the accuracy of this technique has low validity. Further education and simulation can be conducted to improve the quality of this technique.